2015
DOI: 10.1002/art.39257
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐Controlled, Sixteen‐Week Study of Subcutaneous Golimumab in Patients With Active Nonradiographic Axial Spondyloarthritis

Abstract: ObjectiveAxial spondyloarthritis (SpA) is a chronic inflammatory disease characterized by back pain and stiffness. The objective of this study was to determine whether golimumab is superior to placebo in patients with nonradiographic axial SpA.MethodsThis phase III, double‐blind, randomized, placebo‐controlled trial was performed to evaluate subcutaneous golimumab (50 mg) versus placebo in patients ages ≥18 years to ≤45 years who had active nonradiographic axial SpA according to the Assessment of SpondyloArthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
125
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(145 citation statements)
references
References 34 publications
13
125
1
6
Order By: Relevance
“…In addition, their mean SPARCC score was similar, if not higher, to what has been observed in axial SpA in randomized controlled trials (30,31). By contrast, SI joint lesions were more scarce in DISH patients, and SPARCC SI joint scores were much lower.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, their mean SPARCC score was similar, if not higher, to what has been observed in axial SpA in randomized controlled trials (30,31). By contrast, SI joint lesions were more scarce in DISH patients, and SPARCC SI joint scores were much lower.…”
Section: Discussionsupporting
confidence: 75%
“…The mean age of the trial population was 31.2 years (SE = 0.51 years) and 57.1% were male. As expected, disease activity was high for this group of patients (mean BASDAI = 6.5) [18]. Golimumab was associated with better clinical outcomes than conventional therapy, as demonstrated by significantly higher proportions of patients in the golimumab group achieving BASDAI50, ASAS20, and ASAS40 responses (median OR = 3.2, 3.6, and 6.0, respectively).…”
Section: Resultssupporting
confidence: 70%
“…GO-AHEAD, a 16-week, phase 3, placebo-controlled randomized trial, demonstrated the efficacy and tolerability of golimumab in patients with nr-axSpA who were not responding to NSAIDs [18]. Significantly more patients in the golimumab group achieved ASAS 20% response criteria (ASAS20), compared with the placebo group at week 16 (71.1 vs. 40.0%, P \ 0.0001), when looking at the full analysis set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, the Assessment of Spondyloarthritis international Society (ASAS) developed a preliminary definition of clinical remission-ASAS partial remission (ASAS PR), which includes assessment of 4 domains: patient global, spinal pain, physical function, and "inflammation" (a proxy for true inflammation, based on morning stiffness) 5 . In clinical trials, 12-15% 5,6 of patients with ankylosing spondylitis (AS) receiving nonsteroidal antiinflammatory drugs (NSAID) achieve partial remission; a ceiling of ~15-40% at 6 months also exists with biologic therapies, including tumor necrosis factor (TNF) inhibitors and secukinumab 7,8 (Table 1 [9][10][11][12][13][14][15][16][17][18][19][20] ). Treating patients with short symptom duration may increase the proportion of patients reaching clinical remission to ~50% 9,21,22 .…”
mentioning
confidence: 99%